1993
DOI: 10.1037/0021-843x.102.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion, social skill, and response to negative affect in schizophrenia.

Abstract: The social skills and social perception of schizophrenia patients in response to negative affect was examined as a function of family expressed emotion (EE). Patients participated in a role-play test, a social perception test, and a problem-solving discussion with a family member and were assessed on several measures of symptomatology. EE of family members was evaluated with the Camberwell Family Interview. On the role-play test, patients with less critical relatives became more assertive in response to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 35 publications
3
44
2
Order By: Relevance
“…Inpatient populations suffering from serious mental illness and comorbid psychiatric conditions may display deficits across a broad range of functioning. One study found that patients with schizophrenia who had highly critical relatives (also referred to as expressed emotion) were more unassertive than patients with less critical relatives, suggesting that assertiveness may interact with environmental factors; however, it remains unclear whether lack of assertiveness was due to a skill deficit, anxiety, or both (Mueser et al, 1993). In addition to the potential lack of social skill, social withdrawal has been considered to be a core feature of chronic schizophrenia (Gleser & Gottschalk, 1967;McClelland & Watt, 1968;Weinman, 1967).…”
Section: Serious Mental Illnessmentioning
confidence: 99%
“…Inpatient populations suffering from serious mental illness and comorbid psychiatric conditions may display deficits across a broad range of functioning. One study found that patients with schizophrenia who had highly critical relatives (also referred to as expressed emotion) were more unassertive than patients with less critical relatives, suggesting that assertiveness may interact with environmental factors; however, it remains unclear whether lack of assertiveness was due to a skill deficit, anxiety, or both (Mueser et al, 1993). In addition to the potential lack of social skill, social withdrawal has been considered to be a core feature of chronic schizophrenia (Gleser & Gottschalk, 1967;McClelland & Watt, 1968;Weinman, 1967).…”
Section: Serious Mental Illnessmentioning
confidence: 99%
“…In the general population, women tend to have stronger verbal processing skills (Kimura, 1999; Maccoby & Jacklin, 1974) and emotion recognition skills (Hall, 1984). On role-play tests of social skill, women with schizophrenia demonstrate better performance than men (Bellack et al, 1992; Mueser, Bellack, Morrison, & Wade, 1990; Mueser et al, 1993). Women with schizophrenia have also been found to have more intact abilities for processing emotional prosody and semantics than their male counterparts (Bozikas et al, 2006; Scholten, Aleman, & Kahn, 2007).…”
mentioning
confidence: 97%
“…Parental CRIT has also correlated positively with "belittling and blaming" statements made by parents, and negatively with "disclosing and expressing" and "trusting and relying" (Hubschmid & Zemp, 1989). The way that EOI relates to interactions between parents/ relatives and patients has generally been less consistent across the literature compared to CRIT (Miklowitz et al, 1984;Mueser et al, 1993). Some studies have found that high EOI parents make more intrusive statements (Strachan et al, 1986) or more ambiguous and unclear statements (Hubschmid & Zemp, 1989); others have found that they do not differ in behavioral interactions compared to low EOI parents .…”
mentioning
confidence: 97%